2017
DOI: 10.3892/mmr.2017.6665
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetically silenced PTPRO functions as a prognostic marker and tumor suppressor in human lung squamous cell carcinoma

Abstract: Protein tyrosine phosphatase receptor-type O (PTPRO), a member of the PTP family, has been frequently reported as potential tumor suppressor in many types of cancer. However, the exact function of PTPRO in lung squamous cell carcinoma (LSCC) remains unclear. Bisulfite sequencing and methylation specific polymerase chain reaction (PCR) were used to identify the methylation status of PTPRO in LSCC cells, and quantitative methylation specific PCR was used to evaluate the methylation levels of PTPRO in LSCC patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…We and others reported that methylation is a crucial mechanism that determines PTPRO expression (15)(16)(17)(18). We, therefore, investigated whether PTPRO was methylated in renal cancer cell lines.…”
Section: Methylation Of Ptpro Was Associated With Its Expression and mentioning
confidence: 96%
“…We and others reported that methylation is a crucial mechanism that determines PTPRO expression (15)(16)(17)(18). We, therefore, investigated whether PTPRO was methylated in renal cancer cell lines.…”
Section: Methylation Of Ptpro Was Associated With Its Expression and mentioning
confidence: 96%
“…Similarly, expression of PTPRO truncated isoform (PTPROt) is increased in liver macrophages with the increasing degree of nonalcoholic steatohepatitis [21]. In contrast, PTPRO is down-regulated in injured podocytes and lung squamous cell carcinoma compared with healthy tissues [22,23]. PTPRO may exhibit different expression alterations in different organs or diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Protein tyrosine phosphatase receptor-type O (PTPRO), a protein tyrosine phosphatase receptor, has been reported to be involved in the pathogenesis and progression of lung squamous cell carcinoma ( 4 ), breast cancer ( 5 ), colorectal cancer ( 6 ) and hepatocellular carcinoma ( 7 ). However, few studies have focused on the association between PTPRO and ACS.…”
Section: Introductionmentioning
confidence: 99%